Road Traffic Noise Annoyance and Cardiovascular Disease Risk in Population: A Case Series Study in Kota Bharu, Malaysia - Naim, Faridah; Nasir, Nurin H M (Kesmas, 2024)
Noise pollution can cause annoyance, significantly threatening the population’s health and well-being. This study aimed to find an association between road traffic noise exposure and cardiovascular disease (CVD) risk among residents in Kota Bharu, Malaysia. This descriptive study used a case series approach and surveyed 34 residents in selected residential areas near main roads. An adapted questionnaire was distributed to residents using a purposive sampling method. Questions related to sociodemographic information, self-reporting about CVD, and road traffic noise assessment were asked to investigate the underlying risk factors for CVD. The average score of CVD assessment was classified as moderate risk. No significant association between noise annoyance and CVD was found using multiple linear regression. However, the association between cardiovascular risk and sociodemographic variables, particularly the length of residency at the current address, was statistically significant. Although noise annoyance was not associated with CVD, the length of residency could mediate CVD risk as those living longer in residence might be less vulnerable to the noise. Future longitudinal studies are recommended, which include a noise exposure assessment with a larger sample.